Investigating the association of mechanical restraint with somatic harmful outcomes: national register-based study - Lone Baandrup; Marie Kruse (BJPsych Open)
Background Coercive measures to manage disruptive or violent behaviour are accepted as standard practice in mental healthcare, but systematic knowledge of potentially harmful outcomes is insufficient.